Interpretação e disseminação de contexto: filtragem semântica, projeto arquitetural e estudo de caso em saúde - Maranhão, Guilherme Melo e (2015)
Context-aware computing investigates how to seamlessly enable the interaction among computing devices and the environment, or context, in which they are located in. The literature has defined the life cycle of context data as composed of four phases: acquisition, modelling, reasoning and dissemination. These latter two phases have been strongly influenced by the heterogeneity of published data, as a consequence of the increasing deployment of sensors. A great challenge reported in the literature has been the development of mechanisms for handling and reasoning about sensor data, and also for notifying contextaware applications in an efficient and relevant manner. Aiming to solve this problem, this research focuses on a new approach for semantic context reasoning and filtering in accordance with design principles recommended by the literature. As a result of this work, the main contributions include an extensible and maintainable mechanism for semantic context filtering; the architectural model of a context reasoning component, called Hermes Interpreter (HI); the Hermes Base component, which exposes an API for accessing a publish-subscribe-based communication middleware; and HI’s functional validation and performance evaluation in a simulated scenario of vital signs monitoring in Intensive Care Units and wards. This research demonstrated the efficiency of the behaviour of the semantic filtering mechanism for end users applications. Besides, by increasing the number of subscribers, it was observed that the response time was acceptable in almost all experiments. Despite this, it was also verified the high cost of the semantic filtering processing in comparison with pure context reasoning activities. Regarding the HI component’s architectural design, this work recommends it as a reusable artifact for researches on the subject of context reasoning.